Engineering of an Anti-Inflammatory Peptide Based on the Disulfide-Rich Linaclotide Scaffold - Cobos, Claudia (Biomedicines, 2018)
Inflammatory bowel diseases are a set of complex and debilitating diseases, for which there is no satisfactory treatment. Peptides as small as three amino acids have been shown to have anti-inflammatory activity in mouse models of colitis, but they are likely to be unstable, limiting their development as drug leads. Here, we have grafted a tripeptide from the annexin A1 protein into linaclotide, a 14-amino-acid peptide with three disulfide bonds, which is currently in clinical use for patients with chronic constipation or irritable bowel syndrome. This engineered disulfide-rich peptide maintained the overall fold of the original synthetic guanylate cyclase C agonist peptide, and reduced inflammation in a mouse model of acute colitis. This is the first study to show that this disulfide-rich peptide can be used as a scaffold to confer a new bioactivity.